1999
DOI: 10.1046/j.1529-8817.1999.3530501.x
|View full text |Cite
|
Sign up to set email alerts
|

THE RELEASE OF COPPER‐COMPLEXING LIGANDS BY THE BROWN ALGA FUCUS VESICULOSUS (PHAEOPHYCEAE) IN RESPONSE TO INCREASING TOTAL COPPER LEVELS

Abstract: The growth of Fucus vesiculosus L. germlings in chemically defined culture media containing a range of Cu concentrations (20-1000 nM) was monitored simultaneously with measurement of the Cu speciation in the media by competitive equilibrium-adsorptive cathodic stripping voltammetry. Fucus vesiculosus germlings were found to exude Cu-complexing ligands with conditional stability constants of the order of 1.6 ؋ 10 11 . Ligand concentrations increased with increasing total dissolved Cu concentrations (Cu T ) unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(48 citation statements)
references
References 37 publications
(74 reference statements)
2
46
0
Order By: Relevance
“…For example, Cu toxicity may also be reduced due to detoxification pathway of Cu by the algal cell. Certain algal species, including Scenedesmus acutiformis , Chlorella fusca and Fucus vesiculosis , have been shown to release strong ligands that reduce the bioavailability of Cu in aqueous phase if they are released in sufficient amounts (Robinson, 1989;Gledhill et al, 1999;Rijstenbil and Gerringa, 2002). Cell wall exclusion of Cu and intracellular detoxification by binding to phytochelatins or polyphosphate have also been demonstrated in a variety of freshwater algal species in response to elevated Cu concentrations (Twiss et al, 1993;Knauer et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…For example, Cu toxicity may also be reduced due to detoxification pathway of Cu by the algal cell. Certain algal species, including Scenedesmus acutiformis , Chlorella fusca and Fucus vesiculosis , have been shown to release strong ligands that reduce the bioavailability of Cu in aqueous phase if they are released in sufficient amounts (Robinson, 1989;Gledhill et al, 1999;Rijstenbil and Gerringa, 2002). Cell wall exclusion of Cu and intracellular detoxification by binding to phytochelatins or polyphosphate have also been demonstrated in a variety of freshwater algal species in response to elevated Cu concentrations (Twiss et al, 1993;Knauer et al, 1997).…”
Section: Resultsmentioning
confidence: 99%
“…Eukaryotic phytoplankton (Zhou and Wangersky 1989;Lage et al 1994;Leal et al 1999;Croot et al 2000) and macroalgae (Gledhill et al 1999) have been found to produce extracellular Cu complexing ligands in response to Cu stress. In general, it appears that the organisms producing the strongest chelators are the most sensitive to Cu f .…”
Section: Possible Sources and Sinks Of Cu Complexing Ligands-inmentioning
confidence: 99%
“…To identify possible reasons, the mechanism(s) of resistance in G. longissima need to be elucidated, which are likely to involve a combination of exclusion and tolerance of the metal, as found in several other seaweed species (e.g. Gledhill et al 1999;Garcia-Ríos et al 2007; Contents at the start of the transplantation experiment are also shown.…”
Section: Discussionmentioning
confidence: 99%